2020
DOI: 10.1002/pros.24030
|View full text |Cite
|
Sign up to set email alerts
|

Can ultrasound irradiation be a therapeutic option for prostate cancer?

Abstract: BackgroundFocal therapies for prostate cancer (PC) can reduce adverse events and do not lead to androgen‐independent progression. Ultrasound could be used for cancer treatments if the repetition frequency is fitted to the purpose. We investigated the possible therapeutic effect of ultrasound irradiation on PC cells.Materials and MethodsWe irradiated two PC cell lines, androgen‐dependent LNCaP and ‐independent PC‐3 with ultrasound (3.0 W/cm2, 3 MHz, irradiation time rate: 20%) for 2 minutes for 1 day or 3 conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…The current results show that LNCaP and PC‐3 differ in therapeutic efficacy in vitro, specifically that PC‐3 may be resistant to treatment compared to LNCaP. This trend has been suggested in previous reports 6 . Differences in efficacy by cell type are observed despite the fact that the treatment mechanism is mechanical stimulation, which has also been reported for X‐ray radiation 20 and HIFU combined with radiotherapy 21 .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The current results show that LNCaP and PC‐3 differ in therapeutic efficacy in vitro, specifically that PC‐3 may be resistant to treatment compared to LNCaP. This trend has been suggested in previous reports 6 . Differences in efficacy by cell type are observed despite the fact that the treatment mechanism is mechanical stimulation, which has also been reported for X‐ray radiation 20 and HIFU combined with radiotherapy 21 .…”
Section: Discussionsupporting
confidence: 83%
“…This trend has been suggested in previous reports. 6 Differences in efficacy by cell type are observed despite the fact that the treatment mechanism is mechanical stimulation, which has also been reported for X-ray radiation 20 and HIFU combined with radiotherapy. 21 Not only by cell type but also by time after US irradiation, the therapeutic effect has been observed to vary.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…However, an in vitro study conducted by Maeshige et al. reported that PC-3 and LNCaP cells proliferation was significantly inhibited by US irradiation (3.0 W/cm 2 , 3 MHz) [33] . This seems to be inconsistent with our results.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the outcomes of ICI monotherapy are inadequate due to the poor immunological circumstance [5]. Recently, we found that US irradiation of PC cell lines can induce apoptosis without thermal damage to cancer cells [6]. If the antitumor effect of ICIs on PC is upregulated in the combination treatment with US irradiation, a less invasive and effective treatment of ICIs in clinical practice can be performed.…”
Section: Introductionmentioning
confidence: 99%